1976
DOI: 10.3171/jns.1976.45.1.0009
|View full text |Cite
|
Sign up to set email alerts
|

Multidirectional tomography in cervical spine injury

Abstract: Forty-one patients with acute cervical spine injury were examined by both conventional radiography and multidirectional tomography and the findings compared. Indications for tomography are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1980
1980
2001
2001

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Conventional tomography is still considered the standard investigation of choice for these injuries when a more detailed work-up is required to clarify a questionable radiograph or to gain a better understanding of the fracture pattern [6]. Although conventional tomography delivers excellent visualization of the bony details, a single examination takes 20-30 min [19]. During this period, the patient should lie in the lateral decubitus position to get the optimal picture quality [7].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Conventional tomography is still considered the standard investigation of choice for these injuries when a more detailed work-up is required to clarify a questionable radiograph or to gain a better understanding of the fracture pattern [6]. Although conventional tomography delivers excellent visualization of the bony details, a single examination takes 20-30 min [19]. During this period, the patient should lie in the lateral decubitus position to get the optimal picture quality [7].…”
Section: Discussionmentioning
confidence: 99%
“…This is difficult or even impossible for many patients during the acute work-up of an odontoid fracture [1]. The advantages of the conventional tomogram as an adjunct to the usual investigations for cervical spine injuries are well documented in the literature [17,19]. Investigations by Ehara et al have shown that in 6% of cases the odontoid fracture was not seen on conventional radiographs and could only be visualized using tomography [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations